Heterogeneity of glucose metabolism and uptake identifies distinct cancer cell and cancer stem cell phenotypes - Tylichova, Zuzana; Krkoska, Martin; Hrabal, Vaclav; Stenckova, Michaela; Vojtesek, Borivoj; Coates, Philip J (Cellular & molecular biology letters, 2026)
BACKGROUND: Tumor cells show phenotypic heterogeneity, including a small subpopulation of cancer stem-like cells (CSCs) that are responsible for maintaining tumor growth and metastasis. Altered glucose metabolism is a characteristic feature of cancer cells, which often display increased aerobic glycolysis alongside mitochondrial oxidative respiration (the Warburg effect). However, there is evidence that CSCs exhibit distinct glucose metabolism compared with the tumor cell bulk, with increased mitochondrial activity and oxidative respiration. Thus, identifying individual cells with different modes of glucose metabolism may serve as a common identifier of CSCs, and these metabolic differences would allow selective therapeutic targeting. METHODS: We investigated the levels of enzymes involved in glycolysis and oxidative respiration, together with glucose uptake and mitochondrial membrane potential in individual cancer cells. These parameters were correlated with each other and with CSC markers. RESULTS: We show considerable heterogeneity of metabolic markers in individual tumor cells. Surprisingly, high glucose uptake correlates with high mitochondrial membrane potential, indicating that increased oxidative respiration and aerobic glycolysis coexist rather than showing an inverse correlation. We also show that colonies derived from cells with high mitochondrial membrane potential exhibit heterogeneous metabolic parameters, demonstrating that metabolic profiles are not hard-wired. Public gene expression profiling data indicated similar inconsistent metabolic features of CSCs. CONCLUSIONS: The data reveal inherent heterogeneity and plasticity of glucose metabolism and mitochondrial membrane potential in tumor cells, with evidence for a subpopulation that possesses both increased glucose uptake and increased mitochondrial membrane potential, with implications for therapeutic targeting of metabolism in cancer. GRAPHICAL ABSTRACT: [Image: see text] SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s11658-025-00837-0.
Keywords: LDH; Glucose metabolism; Mitochondria; GLUT1; SDH; ALDH; Cancer stem cells